2014
DOI: 10.1089/humc.2014.027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mildly Acidic pH Conditions on the Production of Lentiviral and Retroviral Vectors

Abstract: Human immunodeficiency virus type 1-derived lentiviral vectors (LVs) are becoming major tools for gene transfer approaches. Several gene therapy clinical studies involving LVs are currently ongoing. Industrial production of clinical-grade LVs is therefore an important challenge. Some improvements in LV production protocols have already been possible by acting on multiple steps of the production process like transfection, cell culture, or media optimizations. Yet, the effects of physicochemical parameters such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Based on the drop in pH post-induction for the GPRTG-EF1α-hγ c -OPT stable cell line in cell factories and studies that have shown transient LVV production to increase at lower pH values, 29 , 31 the effect of maintaining a range of pH set points throughout the vector production phase was investigated. Reactors were inoculated at 15,000 cells/cm 2 (8 × 10 7 cells total) and maintained at pH 7.2 for 5 days.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the drop in pH post-induction for the GPRTG-EF1α-hγ c -OPT stable cell line in cell factories and studies that have shown transient LVV production to increase at lower pH values, 29 , 31 the effect of maintaining a range of pH set points throughout the vector production phase was investigated. Reactors were inoculated at 15,000 cells/cm 2 (8 × 10 7 cells total) and maintained at pH 7.2 for 5 days.…”
Section: Resultsmentioning
confidence: 99%
“…Lower pH has been shown to increase LV production. 26 Therefore, in runs 6–10 pH was decreased to 7.0 after PEI-mediated transfection. Lower pH had a positive impact on functional titer, with the total TU exceeding 1E+10 for the first time ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lower pH levels close to pH 6 have been shown to increase vesicular stomatitis virus envelope glycoprotein G pseudotyped LV productivity. 26 As both cells and LV particles are sensitive to pH changes, the correct pH for LV production is determined by finding the optimal pH value for efficient LV production in the cells in question. In control flasks, pH decreased below 7.0 by the end of culture because of lack of pH control, which indicates that the pH could be decreased also in the bioreactor.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they use PALL iCELLis, a compact fixed-bed bioreactor with an integrated perfusion system, comparing yields achieved with either CaPho precipitation or PEI transfection methods, within a range of pH and under glucose and lactate concentration monitoring. In both transfection methods, they confirmed the critical role of cell density and pH in the efficiency of productivity,57 showing higher production at high cell-density and mildly acidic pH, with vp cm–2 (vp= viral particle) between 1.31E+08 and 4.85E+08 using iCELLis Nano fixed-bed bioreactors.…”
Section: Lentiviral Vectors Manufacturingmentioning
confidence: 55%